2022
DOI: 10.1093/brain/awac341
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary motor area driving changes of structural brain network in blepharospasm

Abstract: Blepharospasm is traditionally thought to be a movement disorder that results from basal ganglia dysfunction. Recently, accumulating morphometric studies have revealed structural alterations outside the basal ganglia, such as in the brainstem, cerebellum, and sensorimotor cortex, suggesting that blepharospasm may result from network disorders. However, the temporal and causal relationships between structural alterations, and whether there are disease duration-related hierarchical structural changes in these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…DTI is a non-invasive method that can effectively observe and evaluate the ultrastructure of WM. Numerous previous studies have reported abnormal GM structures in the basal ganglia, sensorimotor cortex, and cerebellum of patients with blepharospasm ( 66 , 68 ). For example, Martino et al ( 69 ) performed VBM on 25 patients with primary blepharospasm and on 24 healthy controls.…”
Section: Structural and Functional Imagingmentioning
confidence: 92%
See 1 more Smart Citation
“…DTI is a non-invasive method that can effectively observe and evaluate the ultrastructure of WM. Numerous previous studies have reported abnormal GM structures in the basal ganglia, sensorimotor cortex, and cerebellum of patients with blepharospasm ( 66 , 68 ). For example, Martino et al ( 69 ) performed VBM on 25 patients with primary blepharospasm and on 24 healthy controls.…”
Section: Structural and Functional Imagingmentioning
confidence: 92%
“…When interpreting the results of a VBM study, the location of the abnormality is of paramount importance. A comparative study of 62 patients and 62 age/sex matched healthy subjects found that, with an increase in the duration of blepharospasm, the volume of GM increased from the right supplementary motor area (SMA) to the cortical–basal ganglia motor and visual–motor integration pathways, suggesting that blepharospasm is associated with extensive GM structural abnormalities ( 66 ). Another meta-analysis, involving 129 patients with blepharospasm and 144 healthy controls, showed an increase in GM in the bilateral precentral and postcentral gyri, SMA, and bilateral paracenter lobules in patients with blepharospasm, which provides a new concept of blepharospasm as a type of brain network dysfunction ( 67 ).…”
Section: Structural and Functional Imagingmentioning
confidence: 99%
“…In our previous study on BSP, we used a causal structural covariance network (caSCN) to identify two pathways derived by the supplementary motor area—one to areas in the cortico–basal ganglia–brainstem motor pathway and the other to cortical regions in the vision–motor integration pathway. 36 Specifically, the volumes of abnormal thalamic nuclei in patients with BSP were ranked according to JRS and duration, as well as in patients with BSP and with BOD together. These rankings, although not derived from true longitudinal MRIs of the same patients, functioned as a ‘pseudo-time series’ to characterize disease progression.…”
Section: Methodsmentioning
confidence: 99%
“…This methodological extension has yielded significant insights, especially in characterizing the flow of brain information in various neurological conditions. For instance, in temporal lobe epilepsy, schizophrenia, Parkinson’s disease, and Alzheimer’s disease, GCA has demonstrated its utility in elucidating complex brain dynamics 13 – 15 . These applications underscore the versatility and robustness of GCA in diverse research contexts.…”
Section: Introductionmentioning
confidence: 99%